2012
DOI: 10.2131/jts.37.1001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gene expression analysis of 2-aminoanthracene exposed Fisher-344 rats reveal patterns indicative of liver carcinoma and type 2 diabetes

Abstract: -The goal of the present study was to examine hepatic differential gene expression patterns in Fisher-344 rats in response to dietary 2-aminoanthracene (2AA) ingestion for 14 and 28 days. Twenty four post-weaning 3-4 week old F-344 male rats were exposed to 0 mgkg -1 -diet (control), 50 mgkg -1 -diet (low dose), 75 mgkg -1 -diet (medium dose) and 100 mgkg -1 -diet (high dose) 2AA for 14 and 28 days. This was followed by analysis of the liver for global gene expression changes. In both time points, the numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Nrcam is a neuronal cell adhesion molecule that mediates neuron-neuron and neuron-glia adhesion [18]. Furthermore, it was reported that Nrcam was induced in the liver of Fisher-344 rats fed 2-aminoanthracene [19]. Further investigation is needed to clarify the functions of these two genes in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Nrcam is a neuronal cell adhesion molecule that mediates neuron-neuron and neuron-glia adhesion [18]. Furthermore, it was reported that Nrcam was induced in the liver of Fisher-344 rats fed 2-aminoanthracene [19]. Further investigation is needed to clarify the functions of these two genes in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…2AA is categorized as a polycyclic aromatic hydrocarbon (PAH) and as an arylamine [2728]. 2AA can be found throughout the environment, including broiled food and tobacco smoke, as well as in a wide range of products, including coal, tar, crude oil, cereals, grains, flour, vegetables, and pickled foods.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete combustion of fuel, pyrolysis of fossil fuels, and wood and industrial emissions are other sources of PAHs. [12] The Agency for Toxic Substance and Disease Registry (ATSDR) has designated anthracene along with others such as pyrene and phenanthrene as priority PAHs due to their harmful effects, which are representative of other PAHs. Moreover, these PAHs and associated analogs seem to be more harmful, have greater environmental concentration, and present the greatest exposure possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Global gene expression patterns in the liver[2] and pancreas[8] of Fisher-344 (F344) rats’ response to 2AA dietary consumption were previously examined. Differentially expressed transcripts in the pancreas showed proteins to be involved in energy metabolism and protein digestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation